ChemInform Abstract: The Dual Reactivity of 5‐S/5‐O‐Phenyl‐1, 4, 2‐oxathiazoles: A Fragmentation Pathway That Affords Nitriles in the Presence of Water. Issue 47 (November 2015) - Lim, Yi Wee; Hewitt, Russell J.; Burkett, Brendan A.
Abstract: The role of water in the ring‐opening rearrangement of substituted 1, 4, 2‐oxathiazoles towards nitriles is examined.